Knowledge Sharing: Strategi Menumbuhkan Budaya Inovasi Mengembangkan Keterampilan Abad 21 STKIP Al Hikmah Surabaya - Rizka Pratiwi (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
Knowledge sharing is believed to enable us exploring ideas, increasing productivity and innovation to develop an organization. This research is to understand how knowledge sharing and the basis values work at STKIP Al Hikmah. This research is focused on routine briefing activity. This research uses qualitative approach. The research informant technique is the purposive sampling. Data gathering was through observation, interview, literature study and documentation. Data triangulation is from the questionnaire given to all of the academics at STKIP Al Hikmah who join the routine briefing. The analysis used in this research was SECI Model. The result of this research showed that the academic at STKIP Al Hikmah follow all of the knowledge sharing’s stages. All of the four stages were internalized well. This shows through the implementation of knowledge and innovation. Values which become the basis of knowledge sharing is leadership, working values (discipline, responsible, loyal, teamwork and initiative), and also spiritual values. Knowledge sharing gives positive impact for the institution. This is shown by the achievement targets which were successfully reached together